Coal Downstream Potential in Central Kalimantan - Deddy Tanggara; Dody A.K. Wijaya; Wita Kristiana; Nuansa Mare Apui Ganang; I Dewa Made Prawindya Kumara (Asian Journal of Social and Humanities, 2026)
The management and utilization of coal raise new environmental challenges, such as deforestation and land degradation. The issue of global decarbonization requires that coal utilization operate within permitted capacity limits. Based on its diverse characteristics, coal can be utilized as a processed product. Downstream development through advanced coal processing can increase economic value and optimize land use more efficiently. Data were collected from various references, including scientific journals, research reports, government regulations, and related agency documents. The results provide recommendations for coal downstream development, such as optimizing the use of coal as a processed product for the production of methanol and dimethyl ether (DME), which function as alternative fuels and industrial raw materials, as well as synthetic natural gas (SNG) as a substitute for natural gas in various sectors. Coal liquefaction can convert coal into liquid hydrocarbons or fuel oil, thereby increasing its added value. Coal–biomass briquettes can produce smokeless fuel and be used for co-firing in steam power plants (PLTU). Extraction of rare earth elements (LTJ) from coal combustion residues also presents potential, as LTJ have high economic value and are fundamental to modern industries. The application of clean coal technologies, including Integrated Gasification Combined Cycle (IGCC) and Carbon Capture and Storage (CCS), can reduce carbon emissions from coal utilization. Based on these results, diversification of coal utilization through downstream development and clean technologies represents a strategic effort to address environmental challenges and respond to global decarbonization issues in Central Kalimantan Province.